Signalosomes in the Brain: Relevance in the Development of Certain Neuropathologies Such as Alzheimer's Disease - Marin, Raquel (Frontiers in Physiology, 2011)
Emerging data suggest that compartmentalization of signaling molecules into particular membrane compartments, or lipid rafts, may be at the basis of numerous activities related to neuronal preservation against different pathologies. These signaling platforms (signalosomes) are formed by complex lipid and protein that may interact to develop a plethora of different physiological responses upon activation by different extracellular stimuli, thereby contributing to neuroprotection. One of the first studied signalosomes involved in neuroprotection against Alzheimer’s disease (AD) is constituted by estrogen receptor (ER), in association with scaffolding caveolin-1 and a voltage-dependent anion channel (VDAC). In this complex, ER plays a neuroprotective role partially through the modulation of VDAC activation, a porin involved in amyloid beta-induced toxicity. Interestingly, ER and VDAC interactions appear to be altered in lipid rafts of AD brains, a phenomenon that may contribute to neuronal impairment. Alterations in lipid components of these subdomains may contribute to destabilization of this macrocomplex. These recent advances in the relevance of signaling platforms related to brain preservation, in particular against AD, are discussed in this work.